Regional Economic Issues, May 2017, Central, Eastern, and Southeastern Europe : A Broadening Recovery. (Regional Economic Outlook, 2017)
Economic growth is broadening in Central, Eastern, and Southeastern Europe. Further ahead, however, growth prospects are tested by a dwindling workforce and weak productivity. Reaching Western European income levels would thus take longer, says the IMF in its Regional Economic Issues update on the region.